THE USE OF VOLUNTEER SERVICES BY SOCIAL ENTERPRISES IN POLAND - Maria Wojcińska (Research on Enterprise in Modern Economy Theory and Practice, 2014)
Statistical data show that more than three million people are committed to volunteering in Poland, and most of them support the non-profit sector, including social enterprises. The purpose of this article is primarily to show the legal basis of volunteering in Poland, with particular reference to social enterprises; to present the examples of benefits associated with volunteer services; to reflect on the risks relating to an inadequate understanding of the idea of volunteering; and to present the results of selected studies on the use of volunteer services by social economy entities in some provinces in Poland.